Motivasi Karir, Motivasi Ekonomi, Biaya Ujian dan Minat Mahasiswa Memperoleh Sertifikasi Chartered Accountant - Candra Maharani, Putu Monik; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2023)
The research aims to determine the effect of career motivation, economic motivation and exam fees on students' interest in obtaining a Chartered Accountant (CA) certificate. Data analysis used multiple linear regression to answer the research hypothesis. Selection of samples with probability sampling technique obtained as many as 165 respondents. The data source is primary data, with questionnaires distributed via Google Forms. Processing assisted with SPSS 22.0 for Windows. The results showed that career motivation and economic motivation had a positive effect on exam fees and had a negative effect on students' interest in obtaining a Chartered Accountant certificate. Keywords: Student Interests; Career Motivation; Economic Motivation; Exam Fee